THE EFFECT OF DIFFERENT FORMULATIONS OF REBON SHRIMP GRILLED FISH CAKE (Acetes erythraeus) ON CONSUMER ACCEPTANCE - Mushelpi Mushelpi; Suparmi Suparmi; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aims to determine the formula of grilled fish cake (otak-otak) using rebon shrimp (Acetes erythraeus.) flour. This study consisted of 2 stages, namely the manufacture of rebon shrimp flour and determining the best formulation. The method used was experimental with a Completely Randomized Design consisting of 4 levels of treatment of addition shrimp flour, namely: O0 (0 g), O1 (250g), O2 (350g), and O3 (500g), with 3 replicated.Based on organoleptic test showedthat rebon shrimp flour had a significant effect on the taste, aroma, texture, appearance, and color ofgrilled fish cake. The formulation of 350 g of rebon shrimp flour was selected indicated by the value of appearance6.70, smell 7.54, taste 7.29, and texture 7.30. Furthermore, the selectedgrilled fish cake contained moisture, ash, fat, and protein was46.22%, 3.34 %, 4.60%, and 15.39%, respectively.Keywords: Grilled fish cake, Rebon shrimp, Consumer acceptance